2013 IEEE Symposium on 3D User Interfaces (3DUI) 2013
DOI: 10.1109/3dui.2013.6550199
|View full text |Cite
|
Sign up to set email alerts
|

Virtual archery with tangible interaction

Abstract: This paper presents the design of "Virtual Arrow", a 3D simulator for traditional archery. Traditional archers aim without a target figure. Good shooting results require an excellent body-eye coordination that allows the user to perform identical movements during each shot. The fascination of this sport is mainly based on a positive user experience when drawing the bow, focusing the target, releasing the arrow and hitting the target. With our 3D simulator we want to provide a believable archery experience and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…A preliminary study by Thiele et al, created a 3D simulator for traditional archery to try to give users a realistic experience as they practiced motion sequences to develop the best body-eye coordination for accurate shooting. Positive feedback and indications of presence showed that using VR as a training tool was feasible for this application [29]. Other research completed by Mulder et al, created a virtual simulator and feedback indicators for competitive sailing.…”
Section: Vr In Sportsmentioning
confidence: 93%
“…A preliminary study by Thiele et al, created a 3D simulator for traditional archery to try to give users a realistic experience as they practiced motion sequences to develop the best body-eye coordination for accurate shooting. Positive feedback and indications of presence showed that using VR as a training tool was feasible for this application [29]. Other research completed by Mulder et al, created a virtual simulator and feedback indicators for competitive sailing.…”
Section: Vr In Sportsmentioning
confidence: 93%
“…One of the most recent initiatives proposes a VR archery simulator based on a power wall and a real 62" bow [28]. The arrow is not released by the system, as the potential energy is conveyed into a pneumatic tube.…”
Section: State Of the Art 21 Archery In Virtual Reality (Vr)mentioning
confidence: 99%
“…We found four main categories: (1) Learning [3, 4, 12, 15-17, 19, 27, 28, 37-40, 47, 55, 60, 67, 68, 71, 76, 77, 85, 86, 93, 98, 100, 102, 104, 109, 115, 120, 128, 131, 137, 146, 147, 149, 167, 174, 176, 178, 179, 185, 188, 191, 197, 200, 201, 203-206, 210, 212, 217, 218, 223, 225, 227, 229, 239, 240, 242-244, 251, 253, 259], including formal or informal approaches; (2) Health [5, 6, 10, 18, 23, 29, 32, 45, 48, 52, 56-58, 66, 69, 72, 73, 79, 87, 91, 92, 94, 99, 103, 114, 119, 121, 127, 130, 140, 159, 162, 169, 173, 180, 183, 184, 186, 195, 213, 214, 216, 222, 226, 231-233, 238, 245, 247-249, 255], which can be divided into the categories shown in Fig. 3; (3) Accessibility [152,161,202,207,221], including any game that is not in the previous categories and focuses on the inclusion of people with sensory impairments; and ( 4 189,190,193,199,208,228,230,234,235,237,250,254,256,258], which serves as a miscellanea category, where we included analysis of networked commercial games or mobile games that did not pay attention to any of the previous specific areas. This final group of tests included training tools for aircraft pilots, design tools for architects or engineers and analysis of famous commercial games, among others.…”
Section: Exclusion Criteriamentioning
confidence: 99%